Loyalitas Sebagai Faktor Utama Promosi Jabatan Dalam Perspektif Manajemen Islam (Studi Pada Karyawan BRI Syariah KC Palembang) - M Iqbal; Ahmad Syahrizal (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This study aims to find out what factors have the greatest influence on the promotion of positions at BRI Syariah Employees at Palembang Branch Office and analyze it in the perspective of Islamic management. There are two independent variables taken in this study, namely job performance and loyalty of work as the most influential factors on the dependent variable, namely promotion of position. This research uses mixed methods research by combining quantitative and qualitative methods to gain a stronger understanding of the research result. The population in this study amounted to 40 people who were all employees of BRI Syariah KC Palembang. The results of the study showed that loyalty of work had a greater positive effect on job promotions with a significance value of 0.001 <0.05 than job performance with a significance value of 0.033 <0.05. In the perspective of Islamic management, the influence of work loyalty that is greater than work performance does not contradict the principles written in the Koran, namely, faith, piety, balance and justice, and deliberation